Daylight saving time transitions and hospital treatments due to accidents or manic episodes - Lönnqvist Jouko; Haukka Jari; Lahti Tuuli A; Partonen Timo (BMC, 2008)
Abstract Background Daylight saving time affects millions of people annually but its impacts are still widely unknown. Sleep deprivation and the change of circadian rhythm can trigger mental illness and cause higher accident rates. Transitions into and out of daylight saving time changes the circadian rhythm and may cause sleep deprivation. Thus it seems plausible that the prevalence of accidents and/or manic episodes may be higher after transition into and out of daylight saving time. The aim of this study was to explore the effects of transitions into and out of daylight saving time on the incidence of accidents and manic episodes in the Finnish population during the years of 1987 to 2003. Methods The nationwide data were derived from the Finnish Hospital Discharge Register. From the register we obtained the information about the hospital-treated accidents and manic episodes during two weeks before and two weeks after the transitions in 1987-2003. Results The results were negative, as the transitions into or out of daylight saving time had no significant effect on the incidence of accidents or manic episodes. Conclusion One-hour transitions do not increase the incidence of manic episodes or accidents which require hospital treatment.